2022
DOI: 10.1007/s00520-022-06899-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of photobiomodulation for oral mucositis on body weight and BMI of patients with head and neck cancer

Abstract: To evaluate the impact of photobiomodulation for oral mucositis on body weight and Body Mass Index (BMI) of patients with head and neck cancer. MethodsPatients were divided into two distinct groups: Photobiomodulation -PBM (n = 17) and SHAM (n = 19). Participants in the PBM group received the low-power aluminum gallium arsenide (AsGaAl) laser device with maximum output power of 86.7 mW, wavelength of 660 nm (red) and laser applications at 33 different points of the oral mucosa, on alternate days. Patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…All patients showed signi cant differences in weight and BMI throughout the study period, but patients in the PBM group showed less weight loss (p < 0.01) and lower BMI loss (p < 0.01. Although, in this study, PBM did not prevent the onset of oral mucositis, it decreased its severity (p < 0.01) [25].…”
Section: Discussioncontrasting
confidence: 75%
“…All patients showed signi cant differences in weight and BMI throughout the study period, but patients in the PBM group showed less weight loss (p < 0.01) and lower BMI loss (p < 0.01. Although, in this study, PBM did not prevent the onset of oral mucositis, it decreased its severity (p < 0.01) [25].…”
Section: Discussioncontrasting
confidence: 75%
“…More studies about salivary microbiota are required. According to Amanda et al [ 22 ], photobiomodulation for oral mucositis has beneficial effects on preventing weight loss and reducing body mass index in HNC patients who received chemoradiotherapy. Generally, relieving oral mucositis can improve weight loss and nutritional condition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors recommended glutamine to mitigate oral mucositis, there is also a need for highquality studies with a consensus of the methodology to reduce heterogeneity. According to Amanda et al [20], photobiomodulation for oral mucositis also shown positive impact to reduce weight loss and prevented a reduction in BMI in HNC patients who underwent chemoradiotherapy. Relieving oral mucositis can improve weight loss and nutritional status.…”
Section: Discussionmentioning
confidence: 99%